Relationship of Tumor-Associated Macrophage Population Detected by CD68 PG-M1, CD68 KP1, and CD163 with Latent EBV Infection and Prognosis in Classical Hodgkin Lymphoma - Hanife Seda MAVILI; Aydın ISISAG; Ayca TAN; Mine MISKIOGLU; Lale SAKA BARAZ; Nalan NESE (Federation of Turkish Pathology Societies, 2021)
Objective: To evaluate the quantity of tumor-associated macrophages (TAMs) in cases of Hodgkin Lymphoma of classical type (cHL), and to reveal possible associations between TAM intensity and latent Epstein-Barr virus (EBV) infection, overall survival, progression-free survival, prognostic indices, and clinicopathological parameters. Materials and Methods: A total 46 cases of cHL with complete clinical records were selected and re-evaluated histopathologically. Staining for CD68 (PG-M1; KP1 clones) and CD163 was evaluated and the cut-off values were defined. Also, all cases were evaluated using the chromogen in situ hybridization (CISH) method with EBER (Epstein-Barr virus-encoded RNA) probes for the presence of possible EBV infection. Results: It was found that high expression levels of PG-M1 and high International Prognostic Scores (IPS) were associated with shortened overall survival (p=0.047, p=0.013). Cases with 2 or less areas of nodal region involvement were observed to have longer progression-free survival period (p=0.043). Higher expression levels of CD68 PG-M1, CD68 KP1, and CD163 were found to show significant associations with the presence of some clinical parameters such as the presence of B symptoms, spleen involvement, and the presence of EBV infection. Conclusions: Our findings suggest that increase of PG-M1+ TAM is associated with shortened overall survival, while higher expressions of all immunohistochemical markers are statistically significantly associated with the presence of EBV infection and clinical parameters mentioned above. These findings indicate that highlighting the TAM rate via macrophage markers in cases of cHL could be helpful in determining the prognostic risk groups and the relevant results should be mentioned in pathology reports.